An assessment of the impact of physical activity undertaken by patients with gestational diabetes mellitus on neonatal birth weight - Agata Maziarz; Jarosław Ogonowski; Aleksandra Szylińska; Adrian Wiatrak; Agnieszka Turoń-Skrzypińska; Iwona Rotter (Kazimierz Wielki University, 2018)
Background Recent years have seen a growing interest in the physical activity of pregnant patients and its effects on obstetric outcomes. Apart from its positive influence on healthy pregnant patients, moderate physical effort also plays an important role in therapeutic procedures in women diagnosed with gestational diabetes mellitus. The aim of this paper was to assess the link between daily physical activity of patients diagnosed with gestational diabetes mellitus and neonatal birth weight. Material, patients and methods- The study group included 100 patients with gestational diabetes mellitus (GDM) between 26 and 32 weeks' gestation. Their physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), the Pregnancy Physical Activity Questionnaire (PPAQ) and a pedometer. Results No significant correlation between neonatal birth weight and the parameters describing the type and intensity of physical activity was shown. Neonatal birth weight correlated positively with pregravid BMI of the pregnant patient. A negative correlation was identified between gestational weight gain and pregravid BMI. Conclusion There was no relationship between daily physical activity during pregnancies complicated by diabetes mellitus and neonatal birth weight. Maternal pregravid weight was found to be an important parameter affecting the infant's weight.